2014
DOI: 10.1597/11-325
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pathogens Related to Chronic Suppurative Otitis Media in Individuals with Cleft Palate: Bacteriological Culture and Polymerase Chain Reaction

Abstract: Patients with cleft lip and palate with chronic suppurative otitis media presented high frequency of bacterial infection in the middle ear. The classical bacteriological culture did not detect strict anaerobes, whose presence was identified by the polymerase chain reaction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…reported that Pseudomonas aeruginosa was somewhat prevalent in otitis media secretions, while other species, such as S. aureus , E. faecalis , and Proteus mirabilis , occurred at a lower level of frequency ( Weckwerth et al., 2009 ). A later study by the same group found P. aeruginosa to be the most common species and moderately prevalent, and S. aureus to also be prevalent ( Weckwerth et al., 2014 ). Interestingly, when PCR analysis was utilized, the most prevalent species appeared to be F. nucleatum , in nearly 40% of samples ( Weckwerth et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that Pseudomonas aeruginosa was somewhat prevalent in otitis media secretions, while other species, such as S. aureus , E. faecalis , and Proteus mirabilis , occurred at a lower level of frequency ( Weckwerth et al., 2009 ). A later study by the same group found P. aeruginosa to be the most common species and moderately prevalent, and S. aureus to also be prevalent ( Weckwerth et al., 2014 ). Interestingly, when PCR analysis was utilized, the most prevalent species appeared to be F. nucleatum , in nearly 40% of samples ( Weckwerth et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…A later study by the same group found P. aeruginosa to be the most common species and moderately prevalent, and S. aureus to also be prevalent ( Weckwerth et al., 2014 ). Interestingly, when PCR analysis was utilized, the most prevalent species appeared to be F. nucleatum , in nearly 40% of samples ( Weckwerth et al., 2014 ). These studies are in contrast to an earlier publication by Jousimies-Somer and Rintala, in which M .…”
Section: Resultsmentioning
confidence: 99%
“…Weckwerth et al [ 41 ] conducted a study with 31 patients with CLP and chronic suppurative otitis media and obtained positive cultures from 83% of the patients. Pseudomonas aeruginosa (54.9%) , Staphylococcus aureus (25.9%) and Enterococcus faecalis (19.2%) were isolated, but no anaerobes were isolated by culture, and the polymerase chain reaction assays revealed 1 or more bacteria in 97.1% of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Weckwerth et al [39] conducted a study with 31 patients with CLP and chronic suppurative otitis media and obtained positive cultures from 83% of the patients. Pseudomonas aeruginosa (54.9%), Staphylococcus aureus (25.9%) and Enterococcus faecalis (19.2%) were isolated, but no anaerobes were isolated by culture, and the polymerase chain reaction assays revealed 1 or more bacteria in 97.1% of the samples.…”
Section: Discussionmentioning
confidence: 99%